Evolution of Traumatic Parenchymal Intracranial Hematomas (ICHs): Comparison of Hematoma and Edema Components - Wilkes, Sean; McCormack, Erin; Kenney, Kimbra; Stephens, Brian; Passo, Ross; Harburg, Leah; Silverman, Erika; Moore, Carol; Bogoslovsky, Tanya; Pham, Dzung; Diaz-Arrastia, Ramon (Frontiers in Neurology, 2018)
This study seeks to quantitatively assess evolution of traumatic ICHs over the first 24 hours and investigate its relationship with functional outcome. Early expansion of traumatic intracranial hematoma (ICH) is common, but previous studies have focused on the high density (blood) component. Hemostatic therapies may increase the risk of peri-hematoma infarction and associated increased cytotoxic edema. Assessing the magnitude and evolution of ICH and edema represented by high and low density components on computerized tomography (CT) may be informative for designing therapies targeted at traumatic ICH. CT scans from participants in the COBRIT (Citicoline Brain Injury Trial) study were analyzed using MIPAV software. CT scans from patients with non-surgical intraparenchymal ICHs at presentation and approximately 24 hours later (+/- 12 hours) were selected. Regions of high density and low density were quantitatively measured. The relationship between volumes of high and low density were compared to several outcome measures, including Glasgow Outcome Score – Extended (GOSE) and Disability Rating Score (DRS). Paired scans from 84 patients were analyzed. The median time between the first and second scan was 22.79 hours (25%ile 20.11 hours; 75%ile 27.49 hours). Over this time frame, hematoma and edema volumes increased >50% in 34 (40%) and 46 (55%) respectively. The correlation between the two components was low (r=0.39, p=0.002). There was a weak correlation between change in edema volume and GOSE at 6 months (r=0.268, p=0.037), change in edema volume and DRS at 3 and 6 months (r=-0.248, p=0.037 and r=0.358, p=0.005, respectively), change in edema volume and COWA at 6 months (r=0.272, p=0.049), and between final edema volume and COWA at 6 months (r=0.302, p=0.028). To conclude, both high density and low density components of traumatic ICHs expand significantly in the first 2 days after TBI. In our study, there does not appear to be a relationship between hematoma volume or hematoma expansion and functional outcome, while there is a weak relationship between edema expansion and functional outcome.